2021
DOI: 10.1093/geront/gnab112
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Cognitive Function: An Evaluation of Social Bridging and Bonding Mechanisms

Abstract: Background and Objectives Social connectedness has been linked prospectively to cognitive aging, but there is little agreement about the social mechanisms driving this relationship. This study evaluated nine measures of social connectedness, focusing on two forms of social enrichment – access to an expansive and diverse set of loosely connected individuals (i.e., social bridging) and integration in a supportive network of close ties (i.e., social bonding). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 77 publications
1
24
0
Order By: Relevance
“…Any decline in cognitive performance may be important, but we focus on when people no longer manifest normal cognition, a common outcome in the literature on SMD (Kaup et al, 2015;Mayeda et al, 2016;Reisberg et al, 2010). The loss of normal cognitive functioning is clinically significant, especially for early therapeutic intervention (Ritchie & Touchon, 2000), and consequential to the older person's social ties (Perry et al, 2021).…”
Section: Related Research and Study Rationalementioning
confidence: 99%
“…Any decline in cognitive performance may be important, but we focus on when people no longer manifest normal cognition, a common outcome in the literature on SMD (Kaup et al, 2015;Mayeda et al, 2016;Reisberg et al, 2010). The loss of normal cognitive functioning is clinically significant, especially for early therapeutic intervention (Ritchie & Touchon, 2000), and consequential to the older person's social ties (Perry et al, 2021).…”
Section: Related Research and Study Rationalementioning
confidence: 99%
“…Active engagement at the organizational level may reflect an unmeasured social bridging effect of expansive and diverse informal ties on cognitive reserve. For instance, Perry et al (2021, p. 7) maintain that “contact with a larger and more diverse group of peripheral others” increases cognitive reserve that may protect global cognitive function, episodic memory, and executive function. Frequent organizational activities may afford a way to socialize with such peripheral ties.…”
Section: Discussionmentioning
confidence: 99%
“…The interviewer recorded responses using a computer-assisted personal interview. Although the NSHAP also collected measures of olfactory threshold ( n- butanol sensitivity), this study focused on olfactory identification given its stronger association with cognitive outcomes (including executive functioning and semantic memory) (Hedner et al, 2010) and the shared neural structure involved in olfactory identification and social, interpersonal factors (Blumen & Verghese, 2019; Perry et al, 2021; Xu et al, 2020). Following prior studies, olfactory functioning was measured as the sum of correctly identified odors (range: 0-5).…”
Section: Methodsmentioning
confidence: 99%
“…More complex social environments provide greater social stimulation and diverse experiences, the heterogeneity and novelty of which protect against cognitive decline (Cohn-Schwartz et al, 2021). Indeed, managing the different social roles that more complex network structures demand can itself be more cognitively challenging than managing more homogeneous networks that demand less transmittal of information (Perry et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation